Analisis Permasalahan Pengadaan Aset Tetap Tanah Sekolah Luar Biasa di Dinas Pendidikan Provinsi Jawa Barat - Fadhlan Ahmadi; Darya Setia Nugraha (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This research aims to find out how the school land fixed asset procurement system is currently running by the West Java Provincial Education Office for SLB Centra 2 PK PLK Cimahi City and the problems in it, as well as analyze recommendations for the land fixed asset procurement system so that land fixed assets procurement is immediately carried out. This research method is descriptive qualitative research.. Data collection techniques in this research used triangulation techniques by combining interviews, observations, and document studies. The data analysis technique in this research used the Root Cause Analysis method. The results of this research indicate that this land acquisition system is guided by Government Regulation No. 19 of 2021 concerning the Implementation of Land Procurement for Public Interest. However, the method and process, leadership, and external factors caused delays in the implementation of land acquisition. The recommendation for this problem is that the Principal of SLB Centra 2 PK PLK Cimahi City immediately resubmits the land acquisition proposal to the Regional VII Education Office Branch Office, re-budgets land acquisition in its entirety or in stages, or conducts procurement not by buying such as asset utilization unused local government agencies and transfer ownership of local private schools to public schools, and utilize electronic procurement services in the acquisition of school land.